A novel device for in-situ force measurements during laser powder bed fusion (L-PBF). Issue 7 (5th July 2021) - Magana Carranza, Rodrigo; Robinson, Joseph; Ashton, Ian; Fox, Peter; Sutcliffe, Christopher; Patterson, Eann
Abstract : Purpose: The purpose of this paper is to detail the design and first use of a force transducer device to study the development of forces during the laser-powder bed fusion (L-PBF) process from which residual stresses can be inferred. Design/methodology/approach: The proposed novel device consists of an array of load cells for in-situ measurement of forces over time during the L-PBF additive manufacturing process. Measurements of the developed forces layer by layer were recorded in a first build using a 67-degree rotating scan strategy using Inconel 625 build material. Findings: Preliminary experimental results from in-situ measurements using a 67-degree rotating scan strategy showed that the forces induced in the first five layers represented approximately 80% of the maximum on completion of the build and were distributed such as to induce concave deformation of the part, i.e. tension in the centre and compression at the edges of the part. Originality/value: This paper describes a novel device for in-process measurement of the spatial distribution and time-varying nature of the forces induced during the L-PBF process as well as an evaluation of the residual forces following the completion of the build.